Biofortification: Effect of Iodine Fortified Food in the Healthy Population, Double-Arm Nutritional Study - Baldassano, Sara; Di Gaudio, Francesca; Sabatino, Leo; Caldarella, Rosalia; De Pasquale, Claudio; Di Rosa, Luigi; Nuzzo, Domenico; Picone, Pasquale; Vasto, Sonya (Frontiers in Nutrition, 2022)
It is estimated that one-third of the world’s population lives in areas where iodine (I) is scarce and its deficiency is responsible for many related disorders, such as goiter, reproductive failure, hearing loss, growth impairment, congenital I deficiency syndrome, and numerous kinds of brain injury. Mineral deficiencies can be overcome via dietary diversification and mineral supplementation. An alternative or even complementary way is represented by the intake of biofortified foods, which can tackle this lack of micronutrients. In this short-term double-arm nutritional intervention study, a cohort of ten people was supplemented with curly endive leaf biofortified with I and ten people with curly endive without biofortification (Intervention Study on Iodine Biofortification Vegetables (Nutri-I-Food – Full-Text View - ClinicalTrials.gov). The effects on whole-body homeostasis and specifically on I, glucose, lipid, and hepatic, iron metabolism was investigated. Blood samples were obtained at baseline and after 12 days of supplementation with curly endive and compared with controls. Hematochemical and urinary parameters were analyzed at baseline and after 12 days. The results showed that short-term I curly endive intervention did not affect the whole body homeostasis in healthy people and revealed an increase in I concentration in urine samples and an increase in vitamin D, calcium, and potassium concentration in blood samples only in the biofortified cohort respect to controls. This study suggests that short-term consumption of I curly endive crops is safe and could positively impact body health.